1985
DOI: 10.1520/jfs11029j
|View full text |Cite
|
Sign up to set email alerts
|

Fatal In Utero Salicylism

Abstract: An aspirin overdose by an eight-month primigravida proved to be the mechanism of death for the fetus. Clinical progress of the mother and postmortem concentrations of salicylate in the fetus are listed exhibiting the fetal survival time of about 18 to 20 h post ingestion by the mother.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The increased sensitivity of the fetus relative to its mother is demonstrated by our patient and three other intrauterine deaths. 1 " 3 The clinical manifestations and management of salicylate poisoning in the adult are well described elsewhere. 4 Toxic doses of aspirin produce stimulation of the respiratory center of the medulla oblongata, uncoupling of oxidative phosphorylation, and interference with acid-base homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The increased sensitivity of the fetus relative to its mother is demonstrated by our patient and three other intrauterine deaths. 1 " 3 The clinical manifestations and management of salicylate poisoning in the adult are well described elsewhere. 4 Toxic doses of aspirin produce stimulation of the respiratory center of the medulla oblongata, uncoupling of oxidative phosphorylation, and interference with acid-base homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 For these physiologic reasons, fetal effects of maternal ASA toxicity can also be extremely detrimental, with reports ranging from nonreassuring fetal heart rate tracing requiring emergency cesarean delivery to fetal demise. [13][14][15] The patient's salicylate and APAP concentrations measured shortly after ingestion suggest that she may have consumed a lower dose of toxins than reported. Although the patient's only apparent symptom of acute ASA overdose was a change in hearing, the fetal effects of these ingestions appeared to be much more significant, with fetal tachycardia and decelerations on fetal heart monitoring.…”
Section: Discussionmentioning
confidence: 81%
“…However, it has been noted that the severity of the intoxication does not always correlate with serum salicylate levels [ 13 ]. While neither our case nor prior cases have met these criteria, the three cases involving fetal demise in utero involved maternal salicylate levels in the 50–60 mg/dL range [ 3 , 4 ], and it has been shown that fetal blood levels are ∼1.5 times maternal levels [ 9 , 11 ]. Furthermore, the neonate eliminates salicylate more slowly due to immature glucuronidation and renal excretory pathways [ 9 , 11 ], and salicylate tends to concentrate in the fetal brain due to a smaller intravascular/intracellular pH gradient in the fetus [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several prior reports of in utero salicylate toxicity, with three involving acute ingestion [ 1 3 ], two of which resulted in intrauterine fetal demise [ 2 , 3 ]. The remaining cases involve chronic daily usage in the last trimester of pregnancy, and in two of such cases [ 4 , 5 ], fetal or neonatal death was the result, one in utero [ 4 ] and one at day of life nine [ 5 ].…”
Section: Discussionmentioning
confidence: 99%